PENGARUH VIRAL MARKETING, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN THRIFTING DI KOTA BENGKULU - Wijayani, Juwita Ayu; Ekowati, Sri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to determine the effect of Viral marketing, product quality, and price on Thrifting purchasing decisions in Bengkulu city (Case study on UMB students of the faculty of economics and business). This research was conducted in January 2025 until completion. The method used in this research is quantitative method. The sample in this study amounted to 78 respondents. Sampling in this study using Purposive Cluster Random Sampling. With multiple linear regression data analysis. Based on the results of this study, it shows that viral marketing variables have a positive and significant effect on purchasing decisions, product quality variables have a positive and significant effect on purchasing decisions and prices have a positive and significant effect on Thrifting purchasing decisions in Bengkulu city for UMB students, faculty of economics and business. Keywords: Viral Marketing, Product Quality, Price, and Purchasing Decisions